P-76 MANIFESTATIONS OF PORTAL HYPERTENSION IN PATIENTS WITH COMMON VARIABLE IMMUNODEFICIENCY: PRELIMINARY DATA - VERONICA GUIDO; Belen Russo; Daniela Chiodi; Nelia Hernandez (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Liver involvement in common variable immunodeficiency (CVID) can be found in 9% to 79% of cases and may lead to reduced survival. Anicteric cholestasis and portal hypertension (PH) were the main hepatic manifestations. We aimed to establish the prevalence and characteristics of PH in patients with CVID under treatment at a primary immunodeficiency clinic of a tertiary-level hospital. Patients / Materials and Methods: A retrospective and descriptive study examined the medical records of patients with confirmed CVID. Results and Discussion: out of the eleven patients with CVID, eight were women, and the median age was 34 years (range 23-72). PH was suspected in five (45.4%), with three patients experiencing clinically significant PH and one case complicated by variceal bleeding. Table 1 compares both groups (with and without PH). Thrombocytopenia was found in most patients, consistent with the higher incidence of splenomegaly. Liver biopsies performed only in two patients with suspected PH excluded cirrhosis but identified regenerative nodular hyperplasia in one case. Both cases had liver stiffness measurements by shear wave elastography, showing a median of 14.2 kPa. No association was identified with other non-infectious complications of CVID (gastrointestinal and pulmonary disease). Conclusions: Liver disease is often underdiagnosed in patients with CVID, with portal hypertension appearing to be frequent. Early screening is essential to avoid severe complications.